Vibration threshold in non-diabetic subjects - Nolte, Svea; van Londen, Marco; Elting, Jan Willem J.; de Greef, Bianca T. A.; Kuks, Jan B. M.; Faber, Catharina G.; Nolte, Ilja M.; Groen, Rob J. M.; Bakker, Stephan J. L.; Groothof, Dion; Lesman-Leegte, Ivonne; Berger, Stefan P.; et al. (PloS one, 2020)
Measuring vibration perception threshold (VPT) accurately classifies and quantifies the severity of loss of vibration perception. A biothesiometer (Bio-thesiometer.sup.® ; Bio Medical Instrument Co, Ohio, USA) appears to be the most suitable tool to determine VPT due to its low inter-rater variability and low occurence of adaption to the sensation. Different VPT values for a biothesiometer have been described, however, specification on age, height and different measurement locations is currently lacking. The objective of our study was to identify determinants of vibration perception in non-diabetic subjects, in order to provide individualized normal values of VPTs for clinical practice. Measurements of the vibration perception were performed on the big toes, insteps, lateral malleoli, and wrists. A total of 205 healthy subjects were included (108 (52.7%) males) with a median [interquartile range] age of 59 [51;64] (range 21-80) years. Mean height was 174.45 ± 9.20 cm and mean weight was 82.94 ± 14.84 kg, resulting in a mean BMI of 27.19 ± 4.00 kg/m.sup.2 . In stepwise forward linear regression analyses, age (st. [beta] = 0.51, p < 0.001) and height (st. [beta] = 0.43, p < 0.001) were found to be the independent unmodifiable determinants of the VPT at the big toe. Regression coefficients for quantiles of the determinants age and height were incorporated in the corresponding regression equations. This study provides equations to calculate age- and height-specific normal values for VPT that can be used in clinical practice and in large research studies.